GAMBARAN KARIES GIGI SULUNG DAN TINGKAT PENGETAHUAN ORANG TUA TERHADAP PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK PRA SEKOLAH DI TK SILA CHANDRA III BATUBULAN TAHUN 2017 - I Gusti Ayu Candra Dewi; I Nyoman Wirata (Jurnal Kesehatan Gigi (Dental Health Journal), 2018)
Dental caries is a dental tissue disease marked by tissue damage, starting from tooth surface spread towards the pulp. The prevalence of caries in children aged 1 until 4 years in Indonesia by 10.4%. Knowledge of parents is very important to underlying the formation of behaviors that support or do not support oral hygiene of children. This study aims to obtain a description of dental caries and the level of parents knowledge of dental and oral health care in preschool children at kindergarten Sila Chandra III Batubulan in 2017. This study uses descriptive research with survei. Performed on children and parents in kindergarten Sila Chandra III Batubulan 2017 which amounted to 60 people. Results of the research on caries deciduous teeth obtained 51 children (85%) suffered dental caries, the mean caries of deciduous teeth is 4.9 and belong to high category. Parents knowledge of the preservation dental and oral health preschoolers with very good category as 24 people (40%), and with the failure category as two people (3.33%). Children of suffering caries deciduous teethbased on the level of knowledge parents obtained results that is 19 children(79%) suffering caries deciduous teeth with the level of knowledge is very good.It is expected to increase promotive efforts that are counseling on how to maintain oral hygiene, dental caries and others in children and the elderly in TK Sila Chandra III Batubulan Year 2017.